Reliability and Economic Effects of Maintenance on TNEP Considering Line Loading and Repair - Mahdavi, Meisam; Monsef, Hassan; Romero, Ruben [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
This paper takes into account the reliability and economic effects of line maintenance on the transmission network expansion planning considering line repairs and the reliability effect of line loadings. For this purpose, a quantitative relationship between line lifetimes and the value of the transmission system is introduced in order to formulate the economic effect of maintenance. Also, the failure rate and mean time to repair coefficients are employed to calculate reliability effects of line maintenance using the cost of load shedding. Furthermore, the effect of line loadings on transmission system reliability is formulated through the line failure rates. The proposed model is tested on the Garver's network and the IEEE Reliability Test System, which is followed by a discussion of the results.
Keywords: Line loading; line maintenance and repair; power system reliability; transmission expansion planning